Analysis of Farmers’ Acceptance Factors for Digital Pond Management Applications Using the UTAUT2 Model - Shiddiq, Muhammad Farras; Dirgahayu, Raden Teduh; Paputungan, Irving Vitra (Research Horizon, 2025)
The shrimp farming industry is crucial to Indonesia’s economy but faces challenges such as declining exports, low productivity, and limited technology adoption. Digital tools have been developed to support pond management through real-time water quality monitoring and data-based decision-making; however, user engagement remains low, indicating a gap between technology provision and adoption. This study aims to analyze factors influencing farmers’ acceptance of such digital technologies using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. A quantitative survey involving 140 shrimp farmers in Central Java was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit significantly affect behavioral intention, while behavioral intention weakly influences actual use behavior, revealing an intention behavior gap. In contrast, use behavior is strongly driven by habit and facilitating conditions, and price value negatively affects intention. The study concludes that habitual use and technical support are more decisive than intention in promoting technology adoption, providing theoretical insights and practical implications for developers to focus on habit-forming design and continuous support for digital transformation in aquaculture.